Perceived Usefulness of Collaborative Digitization of Grey Literature in the Federal Colleges of Education Libraries in North Central Nigeria - Mohammed, Samaila B.; El-Kalash, Kamaluddeen Isa; Barau, Habiba M. (Communicate: Journal of Library and Information Science, 2025)
This study investigated the perceived usefulness of collaborative digitization of grey literature in Federal Colleges of Education (FCE) libraries in North-Central Nigeria. Employing a descriptive research design, the study aimed to find out the current status of grey literature collections, stakeholders’ perceptions on collaborative digitization, barriers to its implementation, and recommendations for optimization. The target population comprised 280 respondents, including College Librarians, library personnel (teaching and non-teaching), and ICT personnel engaged in digitization activities. A structured questionnaire, validated by three experts and yielding a Cronbach’s Alpha reliability coefficient of 0.79 was used for data collection, while descriptive statistics, including mean scores and standard deviations were used to analyze the data. Findings from the study showed that the majority of grey literature available for digitization in the FCE libraries in the study area are student projects with (97.3%), followed by conference papers and proceedings (89.1%). Also, stakeholders strongly perceive collaborative digitization as a useful means of enhancing access to grey literature, particularly through a centralized digital repository (3.30) and increasing availability of grey literature (3.20). Though, the main barriers to collaborative digitization as identified include lack of adequate funding (3.30) and inadequate infrastructure and equipment (3.20). To optimize collaborative digitization, securing adequate funding (3.40) and upgrading infrastructure (3.30) were the top recommendations from stakeholders. Based on the findings, it is recommended among others that establishing a regional consortium among FCE libraries in North-Central Nigeria would facilitate resource sharing and address the institutional gaps, especially for underrepresented types of grey literature such as photographs and artworks.